The Effect of Intellectual Capital and Innovative Work Behavior on Business Performance - Abu Muna Almaududi Ausat; Anna Widayani; Ika Rachmawati; Nunuk Latifah; Suherlan Suherlan (Universitas Hayam Wuruk Perbanas, 2021)
The twenty-first century is a century of knowledge, discovery, and innovation, with rapid advances in science and information technology marking significant developments. The level of competitiveness within organizations is increasing. This truth motivates entrepreneurs to grow in order for their businesses to thrive. The major goal of this research is to examine how intellectual capital and innovative work behavior affect business performance in SMEs. The author then explains the three constructions' conceptual structure. To further understand the relationship between variables, quantitative methods based on Structural Equation Modeling (SEM) and Partial Least Squares (PLS) variance were used. Participants were chosen from SMEs in Yogyakarta, Indonesia, via an online questionnaire. The findings of this research show that intellectual capital and creative work behavior have a positive and significant effect on business performance. SMEs can use intellectual capital to define expected performance and as a tool to evaluate performance to develop employees who will be able to meet the needs of SMEs in the future. Furthermore, it demonstrates that SMEs, not just large corporations, can attain high-performance levels throughÂ synchronizing intellectual capital and innovative work behavior.